The (Un)Believable Truth about Rwanda. Issue 2 (July 2019) - Hitchcott, Nicki
Abstract : Since the Genocide against the Tutsi in Rwanda, a proliferation of fictional and non-fictional narratives has appeared, many of them claiming to represent the truth about what really happened in 1994. These include a small but significant number of Rwandan-authored novels which, this article suggests, invite the reader to accept what I call a "documentary pact". While there is no single version of the truth about what happened in Rwanda, one of the common features of fictional responses to the genocide is an emphasis on truth claims. Drawing on examples of both fictional and non-fictional responses to the genocide, this essay discusses the implications of Rwandan authors' insistence on the veracity of narratives that are sometimes difficult to believe. Emphasizing the importance for Rwandan writers, particularly survivors, of eliciting empathy from their readers, this essay will show that the documentary pact is an effective means of appealing to our shared human experience.